Penerapan Model Pembelajaran Kooperatif Tipe Talking Stick Menggunakan Kartu Soal Terhadap Hasil Belajar Fisika Siswa Kelas X di SMA - Sri Maiyena; Marjoni Imamora; Dina Latifa Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This study aims to determine the application of the talking stick type cooperative learning model using question cards to students' physics learning outcomes. This type of research is a quasi-experimental research, with a posttest only control group design. Sampling used simple random sampling where class X.4 as the experimental class and X.3 as the control class. Collecting data using a cognitive test of learning outcomes in the form of a multiple choice test with 20 questions. Data on the affective and psychomotor domains of students used observation sheets which were analyzed descriptively qualitatively. From the results of the final test, the average final score for the cognitive domain in the experimental class and control class was 73.47 and 66.30, respectively. For the affective domain, the average values obtained by the experimental class and control class are 72.12 and 68.18, respectively. As for the psychomotor domain, the average values for the experimental class and control class are 73.10 and 68.29, respectively. From the hypothesis test that was carried out, it was found that H0 was rejected and H1 was accepted, it can be concluded that